PENGARUH EMOSIONAL, KEMUDAHAN DAN PENGALAMAN PELANGGAN TERHADAP KEPUASAN PELANGGAN DI RUMAH MAKAN DI KOTA SURAKARTA - Ahmad, Sidiq (Riset Manajemen dan Akuntansi, 2022)
Thepurposeofthisstudywastoexaminetheemotionaleffect.The convenienceand customerexperienceofrestoranSurakarta'scustomersatisfaction.Thepopulationin this studywere allcustomersofrestoranSurakartacitywithatotalsample of100people.The dataanalysismethodused includesthe analysisofresearch instrumentsconsistingof validity  tests,  reliability  tests,  classical  assumption  tests,  and  hypothesis  testing.  The resultsofthisstudy partially showthatemotionalcharacteristics haveapositive and significanteffectoncustomersatisfactionatrestoraninSurakartacity ,convenience hasa positiveand  significanteffect  on  customer  satisfaction  at  restoran  inSurakarta  City, customerexperience hasapositive andsignificanteffectoncustomersatisfactionat restoran Surakartacity.